Dual Captures of Colorado Rodents: Implications for Transmission of Hantaviruses - Charles H. Calisher; James E. Childs; William P. Sweeney; K. Max Canestorp; Barry J. Beaty (Emerging Infectious Diseases, 2000)
We analyzed dual-capture data collected during longitudinal studies monitoring transmission and persistence of Sin Nombre virus in rodents in Colorado.Our data indicate that multiple captures (two or more rodents captured in a single trap) may not be random, as indicated in previous studies, but rather the result of underlying, species-specific social behavior or cohesiveness. In the pairs we captured, most often, rodents were of the same species, were male, and could be recaptured as pairs. Therefore, dual captures of rodents, which are unusual but not rare, tend to occur among certain species, and appear to be nonrandom, group-foraging encounters. These demographic and ecological characteristics may have implications for the study of the transmission of hantavirus.